Comprehensive assessment of SrO and CuO co-incorporated 50S6P amorphous silicate bioactive glasses in vitro: Revealing bioactivity properties of bone graft biomaterial for bone tissue engineering applications - Ozarslan, Ali Can; Yucel, Sevil (ELSEVIER SCI LTD, 2023)
Bioactivity is critically important for a glass material to be used in bone tissue engineering, which is stated to be affected by the addition of therapeutic ions such as Sr and Cu. In this study, the findings of a comprehensive in vitro study on the bioactivity of previously produced and characterized in terms of structure, composition and thermal features novel SrO and CuO co-incorporated 50S6P (SiO2-CaO-Na2O-P2O5, SrO-CuO) glasses were discussed. Herein, chemical bond, morphology, composition, and crystallinity changes on the amorphous silicate glasses were investigated using FT-IR, SEM-EDX, and XRD analysis, respectively. Furthermore, quantitative assessment of glass ionic dissolution products concentrations were performed in contact with simulated body fluid by ICP-OES analysis. SrO and CuO co-incorporated 50S6P amorphous silicate glasses showed an appropriate release profile in terms of its ionic products (Si4+: 18.5-32.6, Ca2+: 132.1-234.3, Sr2+: 1.29-2.35, Cu2+: 2.28-3.34, ppm), which resulted in the formation of Ca-P layer and the proceeding of its accumulation, further conformed with FT-IR and SEM-EDX. Furthermore, apatite layer, which consists of crystal apatite ranging in size (6.5-9.8 nm) having different degree of crystallinity percentages (2.5-22.4%), was formed on the glasses surface within 28 days in SBF. The results revealed that Sr incorporation (4.22 wt. %) has an enhancing effect on bioactivity, whereas increased Cu incorporation (0.10-0.26 wt. %) had a relatively inhibitory effect on bioactivity of the glasses. These findings are indicators of desirable bioactive features of 50S6P glasses. Thus, these bioactive glasses are acceptable to be utilized in bone tissue engineering application as bone graft biomaterials.
Keywords: Bioactivity behavior; Bone graft biomaterial; Crystal apatite formation; Incorporation of strontium and copper; MELT-DERIVED 45S5; ION RELEASE; ENHANCED BIOACTIVITY; DISSOLUTION BEHAVIOR; MECHANICAL-BEHAVIOR; CERAMIC SCAFFOLDS; CALCIUM-PHOSPHATE; STRONTIUM; APATITE; DIFFERENTIATION; Materials Science